IMPROVING STUDENT'S COGNITIVE LEARNING OUTCOME THROUGH DISCOVERY LEARNING MODEL IN STRUCTURE AND FUNCTION OF PLANT TISSUES SUBJECT - Nurhayati Dukomalamo; Bahtiar Bahtiar; Arini Zahrotun N (Florea : Jurnal Biologi dan Pembelajarannya, 2019)
Discovery learning model encourages learners to find new knowledge and to look for the solution of problems or odd situations. The model provides an opportunity for students to actively participate in building knowledge that they would gain during learning. The research aims to improve student's cognitive learning outcome and activities through discovery learning model in the subject of the Structure and Function of Plant Tissues in SMP Negeri (Public Junior High School) 4 Ternate. The research is a classroom action research in the academic year of 2018/2019. The action research is conducted in two cycles. The research result indicates that the application of discovery learning model could improve the cognitive learning outcome and learning activities among students at class VIII-4 of SMP Negeri 4 Kota Ternate in the subject of the Structure and Function of Plant Tissues.